An uncommon focal epithelial hyperplasia manifestation - Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Giro, Elisa Maria Aparecida; Pansani, Cyneu Aguiar; Ferrari, Junia; Massucato, Elaine Maria Sgavioli; Spolidório, Luis Carlos (My University, 2009)
Focal epithelial hyperplasia is a rare, contagious disease associated with infection of the oral mucosa by human papillomavirus types 13 or 32, characterized by multiple soft papules of the same color as the adjacent normal mucosa. It mainly affects the lower lip, buccal mucosa, and tongue. The purpose of this case report was to describe a rare verrucallesion located in the upper gingiva that was clinically and histologically consistent with focal epithelial hyperplasia.
Keywords: Focal epithelial hyperplasia; Human papillomavirus; Oral pathology